Lampung Folklore with Scaffolding: Efforts to Strengthen Indonesian Students’ Character - Anwar, Chairul; Saregar, Antomi; Yama, Arifeen; Anugrah, Adyt (Universitas Islam Negeri Raden Intan Lampung, 2022)
Attempts to improve the survival of culture, one of which is legend or folklore. In recent years, the presentation of culture in the form of works through folklore has become less attractive. This research aims to create an interactive book on Lampung folklore that incorporates character values and describes the strengthening of students' character through interactive folklore books incorporate character values. This study employs Borg and Gall's research and development procedure. Data collection methods include direct observation or observation, interviews, questionnaires, focus groups, and a literature review. According to the findings of this study, the construction of scaffolding-based folklore in the Legend of Tulung Naga is quite feasible. It may offer students a thorough grasp of character values. Spiritual qualities, nationalism, independence, and social caring are character traits that can be strengthened after students read the scaffolding-based Lampung folklore book. This development research is believed to be an alternative to developing students’ character at school and home so that future generations might produce better generations. Furthermore, by bringing up folklore, it can automatically preserve local culture.